Combination of community-based vulnerability and adaptation to storm surges in coastal regions of Bangladesh - Younus, Md. Aboul Fazal; Sharna, Sabrina Shahrin (© 2014 World Scientific Publishing Co. Pte Ltd, 2016)
This article was published in the Journal of Environmental Assessment Policy and Management [ © 2014 Imperial College Press ] and the definite version is available at : http://doi.org/10.1142/S1464333214500367 The Journal's website is at: http://www.worldscientific.com/doi/abs/10.1142/S1464333214500367